Analisis Kelayakan Usaha Hita Coffee Bali (Coffee Shop) Di Kota Denpasar - Ni Putu Elysa Widiastari; Ni Ketut Murdani; Ni Putu Andini Desiyanti Laksmi (CV ODIS, 2022)
considered, anything that can affect the company really needs to be taken into account. Through a business feasibility study, the business owner can get information about the current position of his business. This information can be used as a reference for the owner to run his business in the future. The purpose of this business feasibility study is to analyze the feasibility of Hita Coffee's business from various aspects, and use SWOT analysis, as well as determine the effectiveness of the competitive strategy applied. In this business feasibility study using qualitative data analysis techniques, data were obtained through interviews, observations, and documentation, which were conducted at Hita Coffee. The data obtained from the object of research are then directly collected and processed by the author. The stages are carried out by analyzing the feasibility study through aspects including market and marketing aspects, legal aspects, technical aspects, and financial aspects. And to find out the business opportunities for Hita Coffee, the SWOT analysis technique consists of the strengths, weaknesses, opportunities, and threats that exist in this business, and then the data is processed into an internal matrix, an external matrix, an IE matrix, and a SWOT matrix. The results obtained from the IE matrix show that Hita Coffee's business position is in position V with growth which is designed to achieve growth in sales, assets, or profits and a combination of the three. In the SWOT method, an alternative strategy is obtained that should be applied by the company in order to develop existing business opportunities. Based on the financial aspect, the results of the NPV (Net Present Value) of 262,546,296, the IRR (Internal Rate Of Return) value of 54%, and the payback period value of 4.82 so the return on investment is 1 year 5 months which will be completed in second. Thus the results obtained that this business is feasible to run.